2014
DOI: 10.1089/scd.2013.0616
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stem Cells Resolve Airway Inflammation, Hyperreactivity, and Histopathology in a Mouse Model of Occupational Asthma

Abstract: Occupational asthma (OA) is characterized by allergic airway inflammation and hyperresponsiveness, leading to progressive airway remodeling and a concomitant decline in lung function. The management of OA remains suboptimal in clinical practice. Thus, establishing effective therapies might overcome the natural history of the disease. We evaluated the ability of human adipose-tissue-derived mesenchymal stem cells (hASCs), either unmodified or engineered to secrete the IL-33 decoy receptor sST2, to attenuate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
0
13
1
Order By: Relevance
“…For IV administration of MCA‐MSCs, 1 × 10 7 cells were resuspended in 2 ml PBS. Mice were restrained in a Perspex restrainer (Perspex Distribution, Chelmsford, United Kingdom), and 1 × 10 6 cells/200 μl PBS were injected into the tail vein of Sal‐ or Ova‐sensitized/challenged mice, which is a commonly used cell concentration delivered to mice (13, 15, 20, 28). For IN administration of MCA‐MSCs, 1 × 10 7 cells were resuspended in 0.5 ml of PBS.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…For IV administration of MCA‐MSCs, 1 × 10 7 cells were resuspended in 2 ml PBS. Mice were restrained in a Perspex restrainer (Perspex Distribution, Chelmsford, United Kingdom), and 1 × 10 6 cells/200 μl PBS were injected into the tail vein of Sal‐ or Ova‐sensitized/challenged mice, which is a commonly used cell concentration delivered to mice (13, 15, 20, 28). For IN administration of MCA‐MSCs, 1 × 10 7 cells were resuspended in 0.5 ml of PBS.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
“…As such, MSCs can be administered systemically via intravenous (IV) infusion, allowing for a broad distribution (12). Upon administration, MSCs accumulate in the lung (13). MSCs also home to the injured tissue through the expression of the chemokine receptor type 4, and the expression of this receptor is heightened in a proinflammatory environment such as in asthma, enhancing their homing ability (14).…”
mentioning
confidence: 99%
“…Adipose‐derived MSCs were chosen for this study as previous studies have demonstrated that adipose‐derived MSCs are easier to culture in large numbers and share a similar phenotype to bone marrow‐derived MSC . In addition, several studies have demonstrated that adipose‐derived MSCs are capable of reducing airway inflammation, airway hyperresponsiveness, and Th2 cytokine production in a murine model [unpublished data] . Prior to performing this study, the effects of MSCs in an acute model of experimental asthma were assessed longitudinally in a pilot study [unpublished data].…”
Section: Methodsmentioning
confidence: 99%
“…ADSCs are characterized by low immunogenicity and the adaptation of ADSCs to their environment provides a promising direction for future clinical applications (31). Martinez-Gonzalez et al (32), demonstrated that ADSCs protect the alveoli structure in patients with asthma by reducing the inflammation generated by neutrophil granulocytes, reducing IgE secretion and inhibiting lymphocyte infiltration. Additionally, Won et al (33) revealed that local injection of ADSCs promoted hair growth.…”
Section: Discussionmentioning
confidence: 99%